Impact of PD-1 and PD-L1 expression on treatment outcomes in newly diagnosed acute myeloid leukemia patients - Ugur Calis; Merve Aydogan; Guldane Cengiz Seval; Klara Dalva; Selami Kocak Toprak (Leukemia Research Reports)
High expression of immune checkpoint markers may leukemic cells to evade the immune system in AML. This study aimed to investigate the relationship between PD-1/PD-L1 expression and treatment outcomes in AML patients.. The study included 21 patients and 18 healthy volunteers. Non-responders exhibited significantly higher PD-1 expression (MFI) in CD3+ and CD4+ T cells. At the time of diagnosis, bone marrow samples from patients exhibited a significantly higher proportion of PD-1 expression in CD3+, CD4+, and CD8+ T lymphocytes than peripheral blood samples. The results revealed an association between PD-1/PD-L1 expression and clinical traits in newly diagnosed AML patients.